2018
DOI: 10.1136/bmjopen-2016-015492
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate cut-offs asarisk stratification tool for in-hospital adverse outcomes in emergency department patients screened for suspected sepsis

Abstract: ObjectivesWe investigated specific lactate thresholds for adverse outcomes in patients presenting to emergency departments (EDs) with suspected sepsis identified based on the performance of a sepsis screening algorithm.Design and settingA standardised sepsis bundle was implemented across public hospitals in New South Wales, Australia, as a quality improvement initiative. A register of all adult ED presentations (≥18 years) meeting predefined criteria for sepsis was created, using a combination of data linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…The existing literature evaluating lactate as a risk stratification tool for in-hospital mortality has predominantly looked at patients with the diagnosis of sepsis or trauma, raising the question of potential value of lactate use on the ED patient. 35,36 Our study is the first in a large population to show that there is a clinically relevant difference in mortality across both expanded lactate cohorts and age cohorts. A statistical difference in lactate levels between genders was also noted; however, this finding was beyond the scope of this paper and could be explored in future research.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The existing literature evaluating lactate as a risk stratification tool for in-hospital mortality has predominantly looked at patients with the diagnosis of sepsis or trauma, raising the question of potential value of lactate use on the ED patient. 35,36 Our study is the first in a large population to show that there is a clinically relevant difference in mortality across both expanded lactate cohorts and age cohorts. A statistical difference in lactate levels between genders was also noted; however, this finding was beyond the scope of this paper and could be explored in future research.…”
Section: Discussionmentioning
confidence: 82%
“…The use of lactate as a diagnostic indicator, prognostic marker, and/or resuscitation endpoint in patients with various disease states has been well described in the literature and has become routine in ED clinical practice. 11,15,23,[29][30][31][32][33][34][35] However, traditional lactate-level thresholds (low < 2.0 mmol/L; intermediate 2.0 to 3.9 mmol/L; and high ≥ 4.0 mmol/L) have been used to guide care without regard to patient age or underlying disease state. 11 Expansion of these lactate-level thresholds and considerations of age and underlying disease states may prove useful in risk stratification and management decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Australian study disclosed that hyperlactatemia was proven to be more accurate in predicting mortality when compared to hypotension unresponsive to fluid replacement [5]. Shetty et al indicated that lactate levels >2 mmol/L in ED patients who were suspected to have sepsis are to be viewed as a risk predictor [6]. Also, these high levels of lactate was associated with in-hospital mortality rates greater than 10 percent and stay times in ICU longer than 72 hours in patients with respiratory and abdominal infectious foci in this study.…”
Section: Biomarkers In Sepsis: When and How To Use Procalcitonin In Smentioning
confidence: 99%